2010
DOI: 10.1111/j.1600-079x.2010.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the orphan GPR50 protein in rodent and human dorsomedial hypothalamus, tanycytes and median eminence

Abstract: The melatonin receptor family is composed of three members, MT(1) and MT(2) receptors that bind melatonin with high affinity and the orphan GPR50 that does not bind melatonin but shares significant sequence homology with the two other subtypes. In the absence of any known ligand for this orphan receptor, little is still known about its function. We recently reported the development of the first anti-GPR50 antibodies that reliably recognized the recombinant human GPR50. We here used these antibodies to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 33 publications
3
43
1
Order By: Relevance
“…Gpr50 was initially cloned from the pituitary but has since been shown to be expressed in the DMH and tanycytes lining the third ventricle (Reppert et al, 1996; Drew et al, 1998, 2001; Sidibe et al, 2010). Despite high sequence similarity to the melatonin receptor family, Gpr50 does not bind to radiolabeled melatonin (Reppert et al, 1996); however, recent work has shown that it does form heterodimers with the melatonin receptor MT1 to reduce the activity of MT1 itself (Levoye et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gpr50 was initially cloned from the pituitary but has since been shown to be expressed in the DMH and tanycytes lining the third ventricle (Reppert et al, 1996; Drew et al, 1998, 2001; Sidibe et al, 2010). Despite high sequence similarity to the melatonin receptor family, Gpr50 does not bind to radiolabeled melatonin (Reppert et al, 1996); however, recent work has shown that it does form heterodimers with the melatonin receptor MT1 to reduce the activity of MT1 itself (Levoye et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently shown that local infusion of NMU into the third ventricle of photoperiodic rats held in SD upregulated DIO2, thus mimicking the LD state (44). Similarly, the GPR50 receptor, which is homologous to the melatonin receptor MT1 but does not bind melatonin, is expressed in tanycytes (Figure 1) and has been implicated in adaptive thermogenesis and torpor (50). GPR50-null mice are resistant to diet-induced obesity; however, when fasted, they more readily enter a state of torpor.…”
Section: Hypothalamic Tanycytes As Mediators Of Seasonal Cyclesmentioning
confidence: 99%
“…Tanycytes are also known to respond to glucose by releasing ATP Ca 2+ waves, especially if it is applied selectively to cell bodies (Frayling et al 2011). Another interesting feature of tanycytes, suggesting their contribution to energy metabolism, is expression of orphan receptor GPR50—member of melatonin receptor family (Sidibe et al 2010). GPR50 is functionally linked to energy homeostasis, which was proven by observation of knock-out (GPR50 − ) mice having more stable body weight—they were more resistant to obesity induced by high-energy diet and to fasting-induced weight loss (Ivanova et al 2007; Bolborea and Dale 2013).…”
Section: Functional Aspects Of Hypothalamic Neurogenesismentioning
confidence: 99%